Improving Employee Performance through Transformational Leadership and Organizational Commitment - Budi Susanto; Khaeruman Khaeruman (JIBEMA: Jurnal Ilmu Bisnis, Ekonomi, Manajemen, dan Akuntansi, 2026)
PT. Telkom Akses (PTTA), a subsidiary of PT. Telekomunikasi Indonesia Tbk, builds and manages telecommunications network infrastructure across Indonesia. One of its branch offices, PT. Telkom Akses Serang Banten, employs 132 staff who handle fixed-line telephony, internet, data communication, IPTV, network interconnection, and mobile services for hundreds of customers. Employee performance at this branch has drawn attention in recent years, particularly regarding how much leadership style and organizational commitment actually move the needle. This study set out to test both factors separately and together using a quantitative, causal-associative design. Data were collected through a survey of 57 employees, drawn by purposive sampling from a workforce of 132, and analyzed with multiple linear regression. Transformational leadership turned out not to matter much on its own, while organizational commitment did. Taken together, the two predictors explained a modest but statistically significant share of the variance in performance. The practical takeaway is straightforward: at PT. Telkom Akses Serang Banten, building commitment appears to matter more than cultivating a particular leadership style if the goal is better employee performance.